Esophageal Dysphagia in Children: State of the Art and Proposal for a Symptom-Based Diagnostic Approach - Lanzoni, Gloria; Sembenini, Camilla; Gastaldo, Stefano; Leonardi, Letizia; Bentivoglio, Vincenzo Pio; Faggian, Giovanna; Bosa, Luca; Gaio, Paola; Cananzi, Mara (Frontiers in Pediatrics, 2022)
Pediatric esophageal dysphagia (PED) is an infrequent condition that can be determined by a large number of disorders. The etiologic diagnosis is challenging due to overlapping clinical phenotypes and to the absence of pediatric diagnostic guidelines. This review aims to summarize the most relevant causes of ED during childhood, highlight the clinical scenarios of PED presentation and discuss the indications of available diagnostic tools. Available information supports that PED should always be investigated as it can underlie life-threatening conditions (e.g., foreign body ingestion, mediastinal tumors), represent the complication of benign disorders (e.g., peptic stenosis) or constitute the manifestation of organic diseases (e.g., eosinophilic esophagitis, achalasia). Therefore, the diagnosis of functional PED should be made only after excluding mucosal, structural, or motility esophageal abnormalities. Several clinical features may contribute to the diagnosis of PED. Among the latter, we identified several clinical key elements, relevant complementary-symptoms and predisposing factors, and organized them in a multi-level, hierarchical, circle diagram able to guide the clinician through the diagnostic work-up of PED. The most appropriate investigational method(s) should be chosen based on the diagnostic hypothesis: esophagogastroduodenoscopy has highest diagnostic yield for mucosal disorders, barium swallow has greater sensitivity in detecting achalasia and structural abnormalities, chest CT/MR inform on the mediastinum, manometry is most sensitive in detecting motility disorders, while pH-MII measures gastroesophageal reflux. Further studies are needed to define the epidemiology of PED, determine the prevalence of individual underlying etiologies, and assess the diagnostic value of investigational methods as to develop a reliable diagnostic algorithm.